A Bayesian model of design imperfections in online feedback systems and their relative impacts. (1st January 2011) - Zhou, Ming; Cao, Menglin
Recent studies have proposed an overwhelming number of solutions to design imperfections of online feedback systems. However, in what sequence the imperfections should be perfected is yet to be operationalised. In this study, we focused upon the relative damages of design imperfections in order to understand the urgency to deal with each imperfection and develop an operational sequence. The effectiveness of online feedback systems was defined using a Bayesian model. The relative damages were then consistently evaluated using the effectiveness criteria. We concluded that identity changing deserved the highest priority on an auction manager's to do list.